Membrane-associated phospholipase C of Drosophila retina. - Inoue, H.; Yoshioka, T.; Hotta, Y. (Journal of Biochemistry, 1988)
Phospholipase C activities against phosphatidylinositol 4,5-bisphosphate and phosphatidylinositol have been examined using head homogenate of Drosophila visual mutants. In many mutants the enzyme activities were found to be reduced. The activities against both phosphatidylinositol 4,5-bisphosphate and phosphatidylinositol were always affected in parallel among the mutants, while the activities of other enzymes related to phosphatidylinositol metabolism, such as diacylglycerol kinase, were not. The enzyme was concluded to be membrane-associated and was activated maximally at low Ca2+ concentration (10(-7) M), when phosphatidylinositol 4,5-bisphosphate was used as a substrate, while the activity obtained with phosphatidylinositol increased with the Ca2+ concentration up to 10(-4) M. The effects of pH on these two enzyme activities differed to some extent.